2016
DOI: 10.1177/1077546316635935
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of structural nonlinearities employing extremes of dynamic responses

Abstract: Some rights reserved. For more information, please see the item record link above.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…There is a direct correlation between the SSU and SSF for accelerometers 1 and 2 and accelerometer 3, and this correlation only deviates outside two normal quantiles in the Q-Q plot and the tails of the distribution beyond 0.05 in the normal probability plot. This is also representative of the ability to use established statistical markers for monitoring features of interest [31] in an edge setup. Previous research has also indicated that such markers can accommodate traditional, as well as new [32], types of sensors.…”
Section: Three-dimensional Plots Of Each Bolt-loosening Scenariomentioning
confidence: 95%
“…There is a direct correlation between the SSU and SSF for accelerometers 1 and 2 and accelerometer 3, and this correlation only deviates outside two normal quantiles in the Q-Q plot and the tails of the distribution beyond 0.05 in the normal probability plot. This is also representative of the ability to use established statistical markers for monitoring features of interest [31] in an edge setup. Previous research has also indicated that such markers can accommodate traditional, as well as new [32], types of sensors.…”
Section: Three-dimensional Plots Of Each Bolt-loosening Scenariomentioning
confidence: 95%
“…During the vibrational motion of the mass cart, the springs are carefully sheared at a particular time instant, in order to simulate a real-time damage scenario. 46 In the present study, two damage instances are created by shearing two different springs at different time instants. The first damage instant, at t = 13 s , reduces the overall stiffness from 0 . 378 to 0 . 303 N / mm (stiffness reduction of around 19 % ).…”
Section: Experimental Verificationsmentioning
confidence: 99%
“…The second break induces a stiffness alteration of around 17 % , by reducing the equivalent stiffness from 0 . 303 to 0 . 249 N / mm at t = 38 s . 46…”
Section: Experimental Verificationsmentioning
confidence: 99%
“…With diverse and novel output-only real-time methods [34] and markers [35] available for structural health monitoring, it is expected that these methods can eventually help tracking and identifying changes and impacts of implementation of passive control options and possible variations in tuning [1]. Finally, recent works on extreme value analyses for structural health monitoring [36] indicate that such aspects can be relevant and applicable to tracking and marking performance of deployed TLCDs.…”
Section: Figure 20 Herementioning
confidence: 99%